(untitled) (International Journal of Physiotherapy, 2014)
Background: WII Balance Board (WBB) being one of the latest, advanced technologies of high sensitivity in monitoring change in balance over time and owing to, ease of use, and portability, it is being used in physical therapy clinics as a popular substitute for the expensive and complicated force plates to improve dynamic strength and balance. Despite its growing popularity, the WBB’s reliability as an intervention and assessment tool for balance is still being investigated. So this study aims in finding the accuracy of WBB. The objectives of the study are to find the Intraclass Correlation Coefficient and Standard Error Measurement on both day 1 and day 2 with eyes closed and eyes open in older adults. Method: 30 subjects over the age of 65 years were assessed for balance using WBB. Subjects were measured in double limb stance with eyes open and closed with feet comfortably distant apart on the board. The same procedure was repeated after 24 hours. Results: The study showed to be statistically significant for eyes open on day 1 and day 2, but was not statistically significant for eyes closed on day 1 and day 2. Conclusion: The study suggested that the WBB was reliable for eyes open and not reliable with eyes closed.